2015
DOI: 10.1002/ijc.29495
|View full text |Cite
|
Sign up to set email alerts
|

Thymidylate synthase expression in circulating tumor cells: A new tool to predict 5‐fluorouracil resistance in metastatic colorectal cancer patients

Abstract: Thymidylate synthase (TYMS) is an important enzyme for 5-fluorouracil (5-FU) metabolism in metastatic colorectal cancer (mCRC) patients. The search for this enzyme in circulating tumor cells (CTCs) can be a powerful tool to follow-up cancer patients. mCRC patients were enrolled before the beginning of 5-FU-based chemotherapy. The blood was filtered on Isolation by Size of Epithelial Tumor Cells (ISET), and the analysis of TYMS expression in CTCs was made by immunocytochemistry. Additionally, we verified TYMS s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 50 publications
1
38
0
Order By: Relevance
“…In patients with metastatic colorectal cancer, thymidylate synthase expression in CTCs has been studied as a potential marker of resistance to 5-fluorouracil (41). Immunofluorescent markers have been used to study androgen receptor (AR) signaling in CTCs from patients with metastatic prostate cancer to tailor hormonal treatment approaches (42).…”
Section: Ctc Characterizationmentioning
confidence: 99%
“…In patients with metastatic colorectal cancer, thymidylate synthase expression in CTCs has been studied as a potential marker of resistance to 5-fluorouracil (41). Immunofluorescent markers have been used to study androgen receptor (AR) signaling in CTCs from patients with metastatic prostate cancer to tailor hormonal treatment approaches (42).…”
Section: Ctc Characterizationmentioning
confidence: 99%
“…The US Food and Drug Administration has validated them as monitoring markers, as they may predict response to treatment (16). Circulating DNA is also considered as a promising type of prognostic marker.…”
Section: Crc and Biomarkersmentioning
confidence: 99%
“…Reinforcing the concept of different resistance mechanisms, we previously carried out a subpopulation of this study for the presence of TYMS staining in CTCs, to associate with tumor resistance to 5‐FU agents . Interestingly, we found that none of the patients irinotecan‐resistant belonged to the population of 5‐FU resistant, indeed highlighting the different mechanisms of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study of our group, we investigated the role of Thymidylate Synthase (TYMS) expression, a protein correlated to tumor resistance to 5‐FU‐based therapy, in CTCs from patients treated with FOLFIRI/FOLFOX/5‐Fluorouracil (5‐FU). All of them received 5‐FU‐based chemotherapy, so we focused on TYMS expression.…”
mentioning
confidence: 99%